Comparing the results of invasive candidiasis prevention with anidulafungin vs. the lipid formulation of amphotericin B in high-risk patients in the early postoperative period after liver transplantation - S. V. Zhuravel; N. K. Kuznetsova; I. I. Utkina; M. S. Novruzbekov; P. V. Gavrilov; T. V. Chernenkaya; G. K. Ospanova (Трансплантология (Москва))
Introduction. The development of invasive candidiasis leads to high mortality after liver transplantation. Choosing an effective prophylaxis is an important task.The study purpose was to compare the results  of invasive candidiasis prevention with anidulafungin vs. the lipid formulation of amphotericin B in high-risk patients in the early postoperative period after liver transplantation. Material and methods. The study included 80 patients with risk factors for the development of invasive mycosis who underwent liver transplantation. Patients were divided into 2 groups. In the first group (n = 40), anidulafungin was prescribed for prophylaxis; in the 2nd group (n = 40), the lipid complex of amphotericin B was used.Results. The most common of Candida spp. isolated in the patients of our study, as expected, was Candida albicans accounting for 31.2%, significantly less than a half. Neither fungal infection breakthrough nor invasive mycosis development were reported in any patient. In group 2, renal replacement therapy was significantly more frequently used. In two cases, the amphotericin B lipid complex was canceled and the conversion to echinocandin was undertaken due to the occurrence of adverse events (chills and fever) associated, in our opinion, with the drug used. Conclusions. 1. Patients after liver transplantation with 2 or more risk factors have absolute indications to invasive mycosis prevention. 2. Anidulafungin and the lipid formulation of amphotericin B are effective for prophylaxis and prevention of fungal infection breakthrough. 3. Anidulafungin has an advantage in safety over the lipid formulation of amphotericin B.